Fabrication of a high density graphene aerogel–gold nanostar hybrid and its application for the electrochemical detection of hydroquinone and o-dihydroxybenzene1. Issue 67 (24th July 2015) - Hongxia, Bei; Ruiyi, Li; Zaijun, Li; Junkang, Liu; Zhiguo, Gu; Guangli, Wang
<x xml:space="preserve">Abstract</x> We report the first synthesis of a high density graphene aerogel–gold nanostar hybrid with excellent mechanical and electrical properties and its application in the electrochemical detection of hydroquinone and o-dihydroxybenzene.